2021
DOI: 10.1037/amp0000666
|View full text |Cite
|
Sign up to set email alerts
|

Optimism versus pessimism as predictors of physical health: A comprehensive reanalysis of dispositional optimism research.

Abstract: and HHSN268201600004C. The authors thank the WHI investigators and staff for their dedication, and the study participants for making the program possible. A full listing of WHI investigators can be found at: http://www.whi.org/researchers/Documents%20%20Write%20a%20Paper/WHI%20Investigator %20Long%20List.pdf

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
97
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(119 citation statements)
references
References 58 publications
15
97
6
1
Order By: Relevance
“…[24][25][26][27] Healthy behaviors, considered protective factors for various diseases, are positively related to dispositional optimism. 4,5,[28][29][30] There is a relationship between life satisfaction, dispositional optimism, and health behavior. Previous studies have indicated that both optimism and healthy behavior increase life satisfaction.…”
Section: Introductionmentioning
confidence: 99%
“…[24][25][26][27] Healthy behaviors, considered protective factors for various diseases, are positively related to dispositional optimism. 4,5,[28][29][30] There is a relationship between life satisfaction, dispositional optimism, and health behavior. Previous studies have indicated that both optimism and healthy behavior increase life satisfaction.…”
Section: Introductionmentioning
confidence: 99%
“…The extent to which perceived helpfulness relates to definitions of successful treatment outcomes in clinical trials is difficult to determine. It is clear, though, that the two are overlapping rather than distinct given that perceptions such as those of treatment helpfulness, quality of life, optimism about the future, and purpose in life all relate directly to morbidity 9,38 and mortality. 39,40 Thus, the percep- †Treatment delay (years) = Age at first mania/hypomania treatment -Age at onset of mania/hypomania.…”
Section: Discussionmentioning
confidence: 99%
“…These findings help illuminate the similarities between preterm born and term born adults. Albeit surprisingly, given that preterm born individuals more often report neurocognitive, socioemotional and physical and mental health adversities [ 5 , 10 ], which have individually been linked to lower optimism and higher pessimism [ 19 , 21 24 ]. The lack of differences, however, may reflect that the adulthood follow-ups captured preterm born and term born young adults who fared better and would report less physical and mental health adversities than those who did not participate.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies associate higher optimism with better physical health [ 15 ], exceptional longevity [ 16 ], and decreased risk of mortality [ 17 , 18 ]. A comprehensive meta-analysis found a significant positive association between overall optimism/pessimism with aggregate positive physical health outcome measures [ 19 ]. Optimism has also been associated with lower rates of binge-eating [ 20 ]), better health-related quality of life [ 21 ], more positive daily mood [ 22 , 23 ] and less suicidal ideation [ 24 ].…”
Section: Introductionmentioning
confidence: 99%